Old English libraries : the making, collection, and use of books during the middle ages - Savage, Ernest Albert (New York : Barnes & Noble ; London : Methuen, 1970)
Besides describing how books were made and collected, this book gives an account of what books were read in the Middle Ages and to what extent.
Reprint of the 1911 ed.
Includes index.
Includes bibliographical references: p. 286-290.
rua 30/05/17
Loan
Keywords: Libraries; Books and reading; Book collecting; Manuscripts, Medieval; Library catalogs; Scriptoria; England